Growth, yield and oil quality of adult pedestrian olive orchards grown at four different planting systems - Massenti, Roberto; Ioppolo, Antonino; Carella, Alessandro; Imperiale, Valeria; Lo Bianco, Riccardo; Servili, Maurizio; Selvaggini, Roberto; Caruso, Tiziano (Frontiers in Plant Science, 2024)
This study evaluated growth, yield and olive oil quality of mature pedestrian olive orchards. Calatina, Nocellara del Belice and Abunara trees were planted at four growing systems. Trees at 2×5 m were trained to central leader (CLx2), those at 3×5 m to free palmette (FPx3), those at 4x5 to globe vase (GVx4), and those at 5x5 to polyconic vase (PVx5). 'Calatina' had the smallest trunk size in all growing sys tems, while canopy size of trees at higher densities was similar for all three cultivars. 'Calatina' was also the most growth efficient and produced the least amount of pruning wood in the hedgerow systems (CLx2 and FPx3). Fruit yield per tree tended to be higher in more vigorous cultivars (Abunara and Nocellara) grown to 3D systems (GVx4 and PVx5), while 'Calatina' was the most yield efficient especially in the hedgerow systems. Fruit and oil yield per ha and average production value tended to be highest in CLx2 trees and lowest in GVx4 trees, with 'Calatina' showing the sharpest changes and 'Nocellara' the smallest changes among growing systems. The growing system did not affect oil fatty acid composition, while 'Calatina' had the highest amount of mono-unsaturated fatty acids and the lowest amount of saturated fatty acids. 'Abunara' oils exhibited the highest amount of total phenols in CLx2, while 'Calatina' and 'Nocellara' oils exhibited the highest amount in FPx3 and PVx5. Both, trans-2-hexenal ("cut grass" sensory note) and hexenyl acetate ("floral" sensory note) tended to be lowest in oils from trees grown at CLx2 and highest in those from trees grown at GVx4, showing a somewhat inverse relationship with fruit ripening degree. The outcome of the present study shows that proper combinations of cultivars, planting densities, and training forms may result in efficient intensive systems for growing olive in areas where super-high-density systems cannot be profitable due to agronomic and environmental limitations. Pedestrian growing systems can also be used to exploit olive biodiversity by allowing the use of available local genotypes. For this reason, they may represent an effective and sustainable solution against unexpected climate changes and associated emerging diseases.